Multifunctional laser imaging of cancer cell secretion with hybrid liquid crystal resonators - Gong, Chaoyang (2022)
Laser emission imaging is an emerging technology, which offers immense potential for revealing biological behavior with enhanced light-matter interactions and signal contrast. State-of-the-art lasers mostly provide physical information of cells, without being able to perform various biochemical functions or biological information of cell. Here this need is addressed by introducing hybrid liquid crystal microlaser resonators, an approach for label-free laser emission imaging of secreted molecules associated with various types of cell–environment interaction. Liquid crystal microdroplets are designed as signal amplifiers to report subtle molecular events sandwiched in a Fabry–Pérot microcavity. Through the integration with a galvometer scanner, dynamic information of cell physiological processes is recorded through different lasing wavelengths. The capability of detecting small molecule, redox oxygen species, to larger molecules such as overexpressed proteins is demonstrated by using pancreatic cancer cell line. The capability of monitoring cell responses to anticancer drug is also illustrated. The proposed concept can be extended to multiplexed biolasers for investigating cell signaling, cell–cell interactions, and drug screening.